Biological and Physical Clogging in Infiltration Wells: Effects of Well Diameter and Gravel Pack. Issue 6 (5th May 2021) - Kalwa, Fritz; Binder, Martin; Händel, Falk; Grüneberg, Luzie; Liedl, Rudolf
Abstract: Gravity‐driven infiltration into the shallow subsurface via small‐diameter wells (SDWs), i.e., wells with an inner diameter smaller than 7.5 cm (3 inches) and no gravel pack) has proven to be a cost‐efficient and flexible tool for managed aquifer recharge (MAR), as it provides relatively high recharge rates with minimal construction effort. SDWs have a significantly smaller open filter area than larger diameter wells with gravel pack, making the infiltration of low‐quality waters through these wells more at risk clogging. To investigate their susceptibility for biological and physical clogging, 24 physical models with different well setups were evaluated by infiltrating either nutrient‐poor but turbid water or nutrient‐rich but clear water. The experiments showed that smaller diameters and the lack of a gravel pack increase the well's susceptibility to both kinds of clogging. However, this effect was observed to be much more pronounced for physical than for biological clogging. Our conclusion is that SDWs show severe disadvantages with respect to the infiltration of highly turbid waters in comparison to large diameter wells with a gravel pack. Nevertheless, this disadvantage is much less severe when it comes to the infiltration of clear but nutrient‐rich waters (e.g., treated wastewater). Depending on the economic and geological circumstances of a MAR‐project, this disadvantage could be outweighed by the significantly lower construction costs of SDWs.